2020
DOI: 10.3389/fmicb.2020.579427
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Microbial Interactions Shape Methane-Oxidizing Bacterial Communities in a Stratified Lake

Abstract: In stratified lakes, methane-oxidizing bacteria (MOB) are strongly mitigating methane fluxes to the atmosphere by consuming methane entering the water column from the sediments. MOB communities in lakes are diverse and vertically structured, but their spatio-temporal dynamics along the water column as well as physico-chemical parameters and interactions with other bacterial species that drive the community assembly have so far not been explored in depth. Here, we present a detailed investigation of the MOB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 117 publications
(151 reference statements)
3
20
1
Order By: Relevance
“…While we argue that the affinity for CH 4 is a key factor for explaining the niche differentiation between αand -MO, we do not dismiss the importance of other parameters in explaining the distribution and abundance of the genera. It has been shown that at constant CH 4 concentration, O 2 has a selecting effect on -MO communities (Hernandez et al, 2015) and other variables like light, metals, or nitrogen compounds have had both inhibiting or enhancing effects on CH 4 oxidation depending on the conditions (Rudd et al, 1976;Bédard and Knowles, 1989;Murase and Sugimoto, 2005;Milucka et al, 2015;Guggenheim et al, 2020). However, we could not detect any selection effect for any of the available variables.…”
Section: Ch 4 Affinity Might Define the Relation Between α-Mo And -Mocontrasting
confidence: 79%
“…While we argue that the affinity for CH 4 is a key factor for explaining the niche differentiation between αand -MO, we do not dismiss the importance of other parameters in explaining the distribution and abundance of the genera. It has been shown that at constant CH 4 concentration, O 2 has a selecting effect on -MO communities (Hernandez et al, 2015) and other variables like light, metals, or nitrogen compounds have had both inhibiting or enhancing effects on CH 4 oxidation depending on the conditions (Rudd et al, 1976;Bédard and Knowles, 1989;Murase and Sugimoto, 2005;Milucka et al, 2015;Guggenheim et al, 2020). However, we could not detect any selection effect for any of the available variables.…”
Section: Ch 4 Affinity Might Define the Relation Between α-Mo And -Mocontrasting
confidence: 79%
“…Stratification of lakes is a common seasonal phenomenon of the temperate zone, which is dependent on the depth and the surface area of the lake (Gorham & Boyce, 1989). Stratified lakes show warm and oxygen-rich upper water layers, dominated by cyanobacteria and algae, and colder (anoxic) deeper layers, that harbor heterotrophic biomass-degraders and sulfate-reducing bacteria (Diao et al, 2017(Diao et al, , 2018Guggenheim et al, 2020;Vigneron et al, 2021). In between these layers, the metalimnion can be found, which is formed by decreasing light-intensities and oxygen concentrations (microaerophilic), and an increasing pool of reduced sulfur compounds, creating ideal niches for phototrophic sulfur bacteria and chemolithoautotrophic micro-organisms (Bush et al, 2017;Diao et al, 2017Diao et al, , 2018Jorgensen et al, 1979;Morrison et al, 2017;Nyirabuhoro et al, 2020;Savvichev et al, 2018;Vavourakis et al, 2019;Vigneron et al, 2021;Wörner & Pester, 2019;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…microbial interactions, were also very recently shown to affect the structure of methanotrophic communities, which, however, was beyond the scope of this study (Guggenheim et al . 2020 ).…”
Section: Discussionmentioning
confidence: 99%